ROADMAP PENGEMBANGAN PENANAMAN MODAL WILAYAH GARUT SELATAN KABUPATEN GARUT - Widaningsih, M. (Institut Ilmu Sosial dan Manajemen STIAMI, 2017)
The success of development within the framework of regional autonomy can not be separated from the success of the region in implementing regional economic development. Regional economic development must involve development actors, local governments can not be alone in the development process because local governments have various limitations both human and budgetary resources. Therefore, it requires the involvement of other parties, in this case the private sector or investors. Local government is only responsible more fully in the form of basic policies needed for regional development, one of which is the basic policy of investment development. Garut Regency has the potential of a very large and varied areas. Its natural wealth includes mountains, the jungle, the sea, the coast, rivers, minerals, fertile soil and beautiful panoramas. This potential, if managed properly will be a huge driving factor for the acceleration of regional development.The problem that will be the topic of attention in this study is the issue of the leading business field of potential and investment opportunities that will be offered to investors. Currently, information about the leading business areas is not available as required.Benefits in this study are: Gain a picture of economic potential in the form of commodities / products that exist in Garut regency. Obtained a picture of superior products and potential / investment opportunities selected in Garut regency.The research design used in this study is descriptive analysis. This design aims to obtain a description of the symptoms studied in the present moment. From the results of the picture, then sought answers to solving problems or phenomena that exist.The result of this research is usually to identify the superior potential to be done an investment from various sectors Garut region south of Garut regency.